Perilaku Sehat Masyarakat Priangan Tahun 1911-1942 - Fathia Lestari (Historia Madania: Jurnal Ilmu Sejarah, 2020)
This study aims at describing the healthy lifestyle of residents in Priangan . Healthy lifestyle is one of the behavior aspects involving the activity of mother - children, pattern of maintaining the body health, pattern of healthy food and sanitation. This paper used the mass media as main sources to see healthy behavior in Priangan. Mass media used is to give illustration of the mindset of healthy in society. The research conducted uses a historical method which has four parts, namely heuristic, criticism, interpretation and historiography.Based the sources, there are several things to sum up as follows :Firstly, from the 1911 until 1942 there had been a change in health behavior within the community in Priangan; Secondly, the changes are due the contact with culture, religion, and social structure; Thirdly, the change in health behavior constitutes the impact of cultural socialization from local genius and European Culture; Fourthly, Mass media has played a vital role for communicating the healthy culture in society.